Determining the Risk of Developing Rheumatic Heart Disease Following a Negative Screening Echocardiogram - Zimmerman, Meghan; Scheel, Amy; DeWyer, Alyssa; Nambogo, Jane-Liz; Otim, Isaac Omara; Tompsett, Alison; Rwebembera, Joselyn; Okello, Emmy; Sable, Craig; Beaton, Andrea (Frontiers in Cardiovascular Medicine, 2021)
Background: Screening echocardiograms can detect early-stage rheumatic heart disease (RHD), offering a chance to limit progression. Implementation of screening programs is challenging and requires further research. This is the first large-scale study assessing the risk of RHD among previous screen-negative children. Methods: This retrospective cohort study, conducted in Gulu, Uganda, performed school-based echo screening on children ages 5–18 years. Surveys were used to determine which children underwent initial screening 3–5 years prior. Age, gender, and disease severity were compared between cohorts. Relative risk (RR) of RHD was calculated for those with a prior screen-negative echo (exposed cohort) compared to those undergoing first screening (unexposed cohort). Results: Echo screening was completed in 75,708 children; 226 were excluded, leaving 1,582 in the exposed cohort and 73,900 in the unexposed cohort. Prevalence of new RHD was 0.6% (10/1,582) and 1% (737/73,900), in the exposed and unexposed cohorts, respectively. The RR of RHD was 0.64 (95% CI 0.3–1.2, p = 0.15), a nearly 40% reduced risk of RHD in those with a prior negative echo. There was no difference in age or gender between RHD cohorts. All cases in the exposed cohort were borderline/mild; 2.6% of cases in the unexposed cohort had moderate/severe disease. Conclusion: There was no statistical difference in RHD prevalence between previous screen-negative children and children with no prior echocardiogram, however, there was a trend toward decreased risk and severity. This information has important implications for the design of screening programs and the use of screening echocardiograms in endemic RHD regions.